Advanced timber framing : Joinery, design & construction of timber frame roof systems - Chappell, Steve (Brownfield, ME : Fox Maple Press, 2012)
Chappell presents a comprehensive treatise on the history and construction of compound timber frame roof system. Beginning with the history and elements of natural design, he unfolds the process of designing and building joined hip and valley timber frame roof systems from the design and theory through layout and execution. Using geometry and math, mixed with harmonics and musical overtones, this is the most complete work ever on the art and design of compound timber frame joinery.--COVER.
Keywords: Wooden-frame buildings -- Design and construction; Framing (Building)